2013
DOI: 10.5194/bg-10-7599-2013
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of food availability and <i>p</i>CO<sub>2</sub> on planulation, juvenile survival, and calcification of the azooxanthellate scleractinian coral <i>Balanophyllia elegans</i>

Abstract: Abstract. Ocean acidification, the assimilation of atmospheric CO2 by the oceans that decreases the pH and CaCO3 saturation state (Ω) of seawater, is projected to have severe adverse consequences for calcifying organisms. While strong evidence suggests calcification by tropical reef-building corals containing algal symbionts (zooxanthellae) will decline over the next century, likely responses of azooxanthellate corals to ocean acidification are less well understood. Because azooxanthellate corals do not obtain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…In this particular study, high food conditions also seemed to alleviate some of the stress associated with high pCO 2 in the CWC solitary species Balanophyllia elegans. Better nutrition not only favoured calcification, but also increased the number of larvae released and reduced juvenile coral mortality by 5-15% (Crook et al, 2013). A possible role of energy expenditure for reproduction is supported by our observation that, after this experiment was completed, reproduction was observed in 8 polyps, and that this occurred mostly in D. dianthus polyps reared under HF (7 out of 8).…”
Section: Modulating Effect Of Feeding On Oa Stresssupporting
confidence: 64%
“…In this particular study, high food conditions also seemed to alleviate some of the stress associated with high pCO 2 in the CWC solitary species Balanophyllia elegans. Better nutrition not only favoured calcification, but also increased the number of larvae released and reduced juvenile coral mortality by 5-15% (Crook et al, 2013). A possible role of energy expenditure for reproduction is supported by our observation that, after this experiment was completed, reproduction was observed in 8 polyps, and that this occurred mostly in D. dianthus polyps reared under HF (7 out of 8).…”
Section: Modulating Effect Of Feeding On Oa Stresssupporting
confidence: 64%
“…In this particular study, high food conditions also seemed to alleviate some of the stress associated with high pCO 2 in the CWC solitary species Balanophyllia elegans. Better nutrition not only favored calcification, but also increased the number of larvae released and reduced juvenile coral mortality by 5-15% (Crook et al, 2013). A possible role of energy expenditure for reproduction is supported by our observation that, after this experiment was completed, reproduction was observed in eight polyps, and that this occurred mostly in D. dianthus polyps reared under HF (7 out of 8).…”
Section: Modulating Effect Of Feeding On Oa Stresssupporting
confidence: 62%
“…The variability observed in HF treatment could be explained by the different morphological features of the polyps (size, calyx diameter, tentacle crown size), that would allow some corals to feed more efficiently than others. In addition, a food-replete environment may allow corals to reorganize energy allocation in order to increase inter-polyp competition for resources and reproductive success as observed in Crook et al (2013). In this particular study, high food conditions also seemed to alleviate some of the stress associated with high pCO 2 in the CWC solitary species Balanophyllia elegans.…”
Section: Modulating Effect Of Feeding On Oa Stressmentioning
confidence: 69%
“…The upwelling mosaic of the CCLME combined with B. elegans' nonplanktonic larval stage, which restricts gene flow, creates the potential for population variation through local adaptation or phenotypic plasticity when exposed to low pH (Sanford & Kelly, ). Previous research has shown B. elegans to be sensitive to low pH, with juvenile mortality 10%–20% higher under pH 7.6 compared to ambient conditions (pH 8.0) (Crook, Cooper, Potts, Lambert, & Paytan a., ). However, only a single population from Monterey Bay, California, was investigated, where exposure to pH < 7.8 is rare (Evans, Pespeni, Hofmann, Palumbi, & Sanford, ; Kroeker et al, ).…”
Section: Introductionmentioning
confidence: 96%